2018
DOI: 10.1088/1742-6596/1007/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

The diagnose of oil palm disease using Naive Bayes Method based on Expert System Technology

Abstract: Abstract. Expert system is dealt with system that used computer-based human intelligence to overcome particular problem which is commonly conducted by an expert. Frequent problem faced by the farmers of oil palm is the difficulty in defining the type of plant disease. As a result, the delay treatment of plant disease brings out the declining of farm products. An application system is needed to deal with the obstacles and diagnosing the type of oil palm plant disease. The researcher designed an intelligence-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
11
0
3
Order By: Relevance
“…Nababan et al [46] employed NB in an intelligence-based application to diagnose the type of oil palm plant disease. Bayes method was conducted based on the formulation of the recognized symptoms.…”
Section: Naïve Bayes (Nb)mentioning
confidence: 99%
“…Nababan et al [46] employed NB in an intelligence-based application to diagnose the type of oil palm plant disease. Bayes method was conducted based on the formulation of the recognized symptoms.…”
Section: Naïve Bayes (Nb)mentioning
confidence: 99%
“…Nababan et al [7] founded out a system for oil palm where features are extracted using probability function and classification using Naive Bayes is done. It provided 80% accuracy.…”
Section: It Uses Fusion Classification Technique Which Include a Combmentioning
confidence: 99%
“…Studies have also shown that the classification accuracies slightly increased when the training set size was increased [68,69]. The NB classifier was also used to classify oil palm disease on the basis of its symptoms with high accuracy: 80% [25], 84% [70], and 92.25% [71], which showed that the NB classifier is well suited with the oil palm disease classification. Moreover, the classification model using the ML approach gave better results compared to the classification model using a combination of features [21], where the accuracy for multiple levels was 80%.…”
Section: Best Model Comparisonmentioning
confidence: 99%
“…An SVM with a polynomial kernel (soft margin) executed the classification with 95% accuracy. Meanwhile, the naïve Bayes (NB) method was used to diagnose oil palm disease in Indonesia [25] on the basis of various symptoms identified in the leaves, spear, stem, and fruits. According to the results, the diagnosis of oil palm disease was achieved with 80% accuracy.…”
Section: Introductionmentioning
confidence: 99%